Resistance and marginalisation: Islamophobia and the political participation of young Muslims in Scotland. (3rd May 2020) - Finlay, Robin; Hopkins, Peter
ABSTRACT: A growing body of work has examined the different forms of political participation engaged with by young Muslims in a variety of Muslim-minority contexts. However, the factors that shape the political participation of Muslims has been frequently overlooked, with the focus primarily on the varied types of participations. Given that the lived experiences of young Muslims frequently entail distinctive challenges, with a range of discriminations being negotiated, there is a need to examine how such factors shape political participation. In this paper, our focus is primarily on how Islamophobia intersects with, and shapes, the political participations of young Muslims in Scotland. We conceptualise Islamophobia as a form of governmentality and build on existing debates by highlighting how Islamophobic governmentality shapes political participation and how space is central to its operation. We demonstrate that when Islamophobia intersects with political participation, it can discipline and marginalise political agency, but it can also engender political and activist resistance. When it works as a barrier to participation, it is pushing young Muslims into the marginal spaces of society. While political resistance is a process of spatial reorientation, aiming to move young Muslims into more public and visible spaces in order to challenge the marginalisation of Islamophobia.